Total plasma cholesterol profile in superovulated crossbred cattle
Crossbred cows (n = 24) were divided in to 4 groups. The animal of each group were treated on day 7 (day O= day of estrous) with different hormonal preparation viz 500 I.U. hCG (Group 1), 5 mg Es/radio/ valerate (Group II), IO ig GnRH (Group III) l